EFFECT OF MOLECULAR STRUCTURE OF PORPHYRINS ON THEIR SEMICONDUCTING PROPERTIES - Hoang, Mai Ha; Phan, Dinh Long; Ngo, Trinh Tung (Vietnam Journal of Science and Technology, 2016)
In this work, we report on the fabrication of organic field-effect transistors (OFETs) using solution processable semiconducting porphyrins 4TBPZ and 2TBPZ. The effect of semiconductor crystal structure on the performance of OFETs was investigated. These single-crystal devices were revealed to exhibit good performance with a maximum carrier mobility for hole of 0.40 cm2 V-1 s-1 and high current on/off ratios. The present work, representing our continuous efforts in understanding the relationship between molecular structure, crystal packing, and OFET performance of semiconducting porphyrins, will be expected to contribute to the design of new porphyrin derivatives for electronic/optoelectronic applications.